Prenatal abnormal width of the cavum septum pellucidum – MRI features and neurodevelopmental outcome. (17th November 2018) - Cooper, Shiri; Katorza, Eldad; Berkenstadt, Michal; Hoffmann, Chen; Achiron, Reuven; Bar-Yosef, Omer
Abstract: Purpose: The purpose of this study is to describe the morphological characteristics of fetal MRIs and outcome of prenatally-detected abnormal width of the CSP (cavum septum pellucidum). Material and methods: A retrospective study of cases with abnormal width of the CSP demonstrated prenatally on MRI. Data collected included: prenatal history, MRI features, sonographic follow up, and neurodevelopmental outcome. Results: Most of the cases referred (34/39) had an abnormal CSP on MRI. Thirty cases had an abnormal width: 23 had narrow CSP and seven had wide CSP. Only three out of 12 cases that were referred with US diagnosis of absent CSP were confirmed by MRI, the rest had narrow CSP. Follow up was performed in 24 out of 30 cases with an abnormal CSP width; all had normal neurodevelopment. Conclusion: To the best of our knowledge, this is the first study to examine the outcome in narrow and wide CSPs detected prenatally. An abnormal width of the CSP prenatally, without an associated fetal abnormality such as aneuploidy, appears to have normal outcome. MRI should be offered when an absence of the CSP is suspected on US to rule out narrow CSP, which seems to be a benign finding.